CURRENT STATUS AND DEVELOPMENT TRENDS OF RESOURCE POTENTIAL OF INDUSTRIAL ENTERPRISES OF KNOWLEDGE-BASED INDUSTRIES - O. Y. Syrovatskay; I. V. Falina (Дискурс, 2016)
This article discusses the concept of knowledge-based industries and the resource potential of an enterprise, the basic approach to resources classification, current status and key trends in the development of the resource potential of industrial enterprises of knowledge-based industries are analyzed.